JURIDICAL ANALYSIS OF THE APPLICATION OF PUNISHMENT AGAINST PERPETRATORS OF GAS CYLINDER THEFT WITH AGGRAVATING CIRCUMSTANCES (A CASE STUDY OF DECISION NUMBER 204/PID.B/2025/PN BINJAI) - Herbert Jonson Leydeker Silaban; Herlina Hanum Harahap (CV. Barokah Publsiher, 2026)
Based on the results of the study, it shows that the qualifications for aggravated gas cylinder theft reviewed from the Indonesian Criminal Code can be distinguished into ordinary theft and aggravated theft. The judge's consideration of proving the elements of the crime of aggravated gas cylinder theft in decision number 204 / Pid.B / 2025 / PN Binjai has been done well, but there are still shortcomings such as only based on evidence in the form of CCTV recordings, 60 gas cylinders, 1 navy blue t-shirt 1 batik patterned pants worn by the defendant when committing the theft, and the testimony of witnesses who did not see and hear directly the event and only witnessed based on CCTV recordings. Obstacles and constraints in applying criminal penalties to perpetrators of aggravated gas cylinder theft in decision number 204 / Pid.B / 2025 / PN Binjai include the problem of strong evidence, the perpetrator's socio-economic factors, limitations of surveillance technology, as well as aspects of policy and resources of law enforcement officers.